Maḵẖzan-i nikāt, yaʻnī, Taẕkirah-yi shuʻarā-yi Urdū maʻ muqaddamah va intiḵẖāb-i kalām-i Qāʼim - Qāʼim, Muḥammad Qiyāmuddīn, 1726?-1795? (SAMP early 20th-century Indian books project ;, 1929)
Biographical anthology of Urdu poets; includes editorial introduction.